Pendampingan Hukum Investasi Ilegal Di Desa Cangkring Kabupaten Wonogiri - Kurniawan, Itok Dwi; Rustamaji, Muhammad; Septiningsih, Ismawati; Santoso, Bambang; Aldyan, Arsyad; Adhliyati, Zakki (Adi Widya : Jurnal Pengabdian Masyarakat, 2025)
Technological advancements have driven the growth of the financial industry in Indonesia. A more complex financial system provides benefits but also raises issues, such as the rise of illegal investments by business entities without official authorization. Investment involves allocating capital with the expectation of future profits. The growing middle class and economic development in Cangkring Village have increased public interest in investing. Unfortunately, many are tempted by high returns with minimal capital without considering legality. This community service program, as part of the Tri Dharma of Higher Education, aims to educate the public about legally compliant investments. The activities were conducted through lectures and participatory methods. The results indicate that public awareness of investment remains low due to limited financial literacy. Further education is needed to help people distinguish between legal and illegal investments, ensuring they invest safely and in accordance with applicable laws.